2016
DOI: 10.1002/j.0022-0337.2016.80.3.tb06087.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Integrated and Disciplinary Clinical Training Patterns for Dental Interns: Advantages, Disadvantages, and Effect on Students’ Self‐Confidence

Abstract: In China, the five-year program of undergraduate education for stomatology consists of four years of lecture courses and one year of internship focused on clinical training. Dental schools provide this clinical training either in their own clinics (referred to as the one-stage pattern because all forms of practice are completed together) or by placing students in external clinics usually at non-affiliated hospitals (referred to as the three-stage program because the three primary areas are taught separately). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
1
12
0
4
Order By: Relevance
“…When the students were at more advanced stages in the course, the difference in anxiety mentioned above would not have been significant. Similar results were found in other studies in which it became clear that practice and repetition are essential elements for the students to gain confidence …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When the students were at more advanced stages in the course, the difference in anxiety mentioned above would not have been significant. Similar results were found in other studies in which it became clear that practice and repetition are essential elements for the students to gain confidence …”
Section: Discussionsupporting
confidence: 89%
“…As reported by the authors, students from universities with integrated clinics were more independent and felt safer to deal with unexpected circumstances whereas students from universities with non‐integrated clinical curricula showed greater ease in the conduction of specialised procedures. The authors suggested that the best form of curriculum would be one that blends these two forms …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, trends such as outreach teaching experiences and community dental care have proven to be useful adjuncts to meet the increasing demand for well-trained graduates [ 6 ]. All these new educational systems have shown to enhance achievement, acquisition of knowledge, and student professional development [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…From one view, it enables students to look upon the greater image of treating patients and not to focus on one precise problem. Furthermore, patients' needs are met, and health care is provided in a proper sequential manner which is not applicable when a “student-centered approach” is practiced [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, trends such as outreach teaching experiences and community dental care have proved to be a useful adjunct to meet the increasing demand for well-trained graduates [6]. All these new educational systems have shown to enhance achievement, acquisition of knowledge, and student professional development [7,8,9].…”
Section: Introductionmentioning
confidence: 99%